Analysis of Sustainable Tourism Development in the Ijen UNESCO Global Geopark Area - Rahmatin, Leily Suci; Nawangsari, Ertien Rining (E-Journal of Tourism, 2025)
The development of sustainable tourism requires an integrated approach involving collaboration between the government, private sector, local communities, and other stakeholders. This study analyzes the implementation of sustainable tourism principles in the Ijen UNESCO Global Geopark, a conservation area that carries geological, biological, and cultural heritage. Despite being designated as a National Geopark, Ijen still faces structural and policy implementation gaps that hinder its potential to contribute effectively to local welfare and the Sustainable Development Goals (SDGs). The research utilizes a qualitative descriptive approach with data collected through field observations, in-depth interviews with stakeholders in Bondowoso and Banyuwangi, and analysis of relevant documents and policy regulations. Findings reveal that while Ijen Geopark holds significant natural and cultural potential, the management is still largely top-down, lacking local empowerment and participatory planning. The inconsistency in implementing the Regulation of the Minister of Tourism and Creative Economy No. 9 of 2021 on Sustainable Tourism Destinations, and Presidential Regulation No. 9 of 2019 on Geopark Development, highlights a need for contextual planning and stronger alignment with sustainable development frameworks. Additionally, mass tourism trends, limited community involvement, and inadequate entrepreneurship development continue to pose challenges. This study emphasizes the importance of inclusive governance, education, and capacity building to ensure that conservation and development are balanced. Strengthening local participation and aligning tourism policies with SDGs can transform Ijen Geopark into a model of sustainable tourism that empowers communities, preserves heritage, and promotes equitable economic growth.